STUDIES ON THE FOREGUT OF ORTHAGA EX VINA CEA HAMPSON (LEPIDOPTERA: PYRALIDAE) DURING PREPUPAL DEVELOPMENT - NANDANAN, SAVITHA; OLAKKENGIL, JOSEPH LOUIS (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Morphological studies on the foregut of Orthaga exvinacea at its prepupal stage could be divided into pharynx, oesophagus and crop. Histologically the wall of the foregut is composed of peritoneum, muscle layers, basement membrane, epithelium and intima. The epithelium is composed of cuboidal and squamous cells.